Pendidikan Agama pada Remaja Putus Sekolah Perspektif Teori Konstruktivisme di Kampung Baru Lamong Badas Kediri - Sugianto (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study investigates the religious education of teenage dropouts in Kampung Baru Lamong Badas Kediri through the lens of constructivism theory. The objective is to understand how these adolescents engage with their religious education based on their experiences. Employing a phenomenological approach, the research utilized interviews, observations, and documentation, applying taxonomic analysis for data evaluation. Findings reveal that these teenagers exhibit various dimensions of religiosity. Their religious beliefs manifest in a commitment to serving and praying, while religious practices are evident in their adherence to religious rules and avoidance of prohibitions. Additionally, a sense of religious feeling is present as they perceive a close relationship with God, fostering a sense of being watched over. Their religious knowledge is characterized by an understanding of moral distinctions within their faith, and the religious effect is reflected in their interactions with both God and others, shaping their behavior accordingly.